Our Country : Northern Evangelicals and the Union during the Civil War Era - Brodrecht, Grant R., 1965- (Book collections on Project MUSE., 2018)
"By examining Civil War-era Protestantism in terms of the Union, author Grant Brodrecht adds to the understanding of northern motivation and the eventual "failure" of Reconstruction to provide a secure basis for African American's equal place in society. Complementing recent scholarship that gives primacy to the Union, Our Country contends that non-radical Protestants consistently subordinated concern for racial justice for what they perceived to be the greater good. Mainstream evangelicals did not enter Reconstruction with the primary aim of achieving racial justice. Rather they expected to see the emergence of a speedily restored, prosperous, and culturally homogenous Union, a Union strengthened by God through the defeat of secession and the removal of slavery as secession's cause."--Provided by publisher.